2003
DOI: 10.1038/sj.ijo.0802481
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of obesity in postmenopausal women with breast cancer: comparison of genetic, demographic, disease-related, life history and dietary factors

Abstract: BACKGROUND: Obesity in women has been associated with a variety of factors, including genetic predisposition, social class, early age at menarche, exercise, alcohol consumption and diet. Obesity is a risk factor for the occurrence and the recurrence of breast cancer in postmenopausal women, perhaps because of increased exposure to estrogen, insulin and insulin-like growth factors (IGFs). The progesterone receptor (PR) and the steroid hormone receptor coactivator pCIP/ACTR/AIB1/TRAM1/RAC3 (AIB1) are hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
0
33
1
Order By: Relevance
“…In contrast to the results of Wasserman et al, 6 in 140 unrelated postmenopausal subjects, we did not find significant correlations between obesity phenotypes and AAM. The results, however, are consistent with the findings of Kirchengast et al, 47 where postmenopausal women exhibited less significant correlation between fat mass and AAM than premenopausal women.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results of Wasserman et al, 6 in 140 unrelated postmenopausal subjects, we did not find significant correlations between obesity phenotypes and AAM. The results, however, are consistent with the findings of Kirchengast et al, 47 where postmenopausal women exhibited less significant correlation between fat mass and AAM than premenopausal women.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of studies have suggested association between AAM and obesity phenotypes. [1][2][3][4][5][6] In a longitudinal study of the northern Finland birth cohort, the proportions of overweight and obese females were significantly higher in those who had earlier menarche. 3 Consistent with that, Wasserman et al 6 found that early menarcheal ages (o12 years) were associated with the risk for obesity in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its widespread use, the action of TMX on human body weight is controversial. Data from the WHEL (Women's Healthy Eating and Living) clinical trial show that obese women with breast cancer under TMX treatment had a decreased BMI (48). However, measurement of BMI in this study occurred at varying times after breast cancer diagnosis and thus did not necessarily reflect prediagnosis BMI.…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, Wasserman et al [46] observed no association between BMI and disease stage at diagnosis in 301 postmenopausal women of the Women's Healthy Eating and Living study. The same was true for women of any age in another study [47].…”
Section: Discussionmentioning
confidence: 99%